Elemental red phosphorus-based materials for photocatalytic water purification and hydrogen production. Issue 25 (18th June 2020) - Zhu, Yukun; Ren, Jun; Zhang, Xiaoli; Yang, Dongjiang
Abstract : In this review, the recent progress in RP-based materials, including the structure properties, synthesis strategies, and their applications in photocatalytic water purification and splitting is summarized. Abstract : Semiconductor-based photocatalysis is a renewable and sustainable technology to solve global environmental pollution and energy shortage problems. It is essential to exploit highly efficient photocatalyst materials. Recently, Earth-abundant elemental red phosphorus (RP) with broader light-harvesting and appropriate band structure characteristics has been widely studied in photocatalysis. In this review, the crystal and electronic structures of RP ( e.g., amorphous, Hittorf's and fibrous phosphorus) materials are firstly summarized along with the current advancement in the synthesis strategies of RP and RP-based materials in photocatalysis accompanied by a thorough discussion of the applications of RP-based materials in photocatalytic pollutant degradation, bacterial inactivation, and water splitting. Finally, this review also offers some guidance and perspectives for the future design of efficient visible-light-driven photocatalysts.